Arabic Language Education Pedagogical Approaches and Contemporary Challenges - Baiq Indana (Al-Qalam: Jurnal Pendidikan Bahasa Arab, 2025)
Arabic language education has undergone significant transformation in response to changing pedagogical paradigms and contemporary educational demands. Despite its long-standing tradition of grammar-oriented instruction, Arabic language teaching continues to face challenges in developing learners’ communicative competence. This study aims to examine pedagogical approaches employed in Arabic language education and to analyze contemporary challenges affecting their implementation in educational institutions. Using a qualitative descriptive-analytical approach, data were collected through classroom observations, interviews with Arabic language instructors, and analysis of curriculum documents. The findings reveal that structural, communicative, and integrative approaches are commonly applied, with a continued dominance of grammar-based instruction. While structural approaches contribute to grammatical accuracy, they often provide limited opportunities for meaningful communication. Conversely, communicative and integrative approaches demonstrate potential in enhancing learners’ speaking skills, motivation, and contextual language use, although their implementation remains inconsistent. Major challenges identified include learners’ low motivation and speaking confidence, limited pedagogical competence of instructors in applying communicative and technology-enhanced methods, insufficient learning facilities, and curricula that emphasize theoretical knowledge over practical language use. The study highlights the need for a balanced pedagogical framework that integrates communicative practices, technological innovation, and supportive language environments. These findings contribute to ongoing discussions on improving the effectiveness and relevance of Arabic language education in contemporary educational contexts.